Physiological quality of crambe seeds (Crambe abyssinica Hochst, Brassicaceae) produced under different water regimes - Pereira, Kennia Karolline Gonçalves (2022)
The physiological quality of the seeds is an aspect of great relevance for the establishment of a culture. However, plant management conditions during seed production can influence its quality. Given the above, the objective was to evaluate the physiological quality of crambe seeds from plants submitted to different water regimes. The experimental design used was in randomized blocks, composed of five water conditions in the soil, based on field capacity (100, 85, 70, 55 and 40%) that consisted of treatments, with four replications. After harvesting, the seeds were sent to the seed laboratory, processed and then evaluated for water content, germination and vigor. Crambe plants grown in soil water conditions between 59 to 61% of the field capacity produce seeds of better physiological quality, demonstrated by the performance in the germination and vigor tests.